In-vitro cytotoxicity of java tea mediated selenium nanoballs against L6 cell lines - Sivakumar, Chitra; Jeganathan, Karthikeyan (Journal of Drug Delivery and Therapeutics, 2018)
The emergence of Nanotechnology has provided a catholic research in recent years by intersecting with assorted branches of science and forming collision on all forms of life. At present there has been a prodigious excitement in the field of Nano pharmacology to seek the role of Nano selenium in individual healthcare and explains how selenium is a double edged sword in the pathologies of chronic diseases like Diabetes mellitus because of their inferior toxicity and ability to gradually release the bioactive principle and free selenium after ingestion. Thus the present study is an embryonic attempt and was aimed at the adroitful synthesis of selenium nanoballs from the aqueous extract of well known herbal tea leaves namely Java tea (Orthosiphon stamineus)  using selenious acid solution. The synthesized Selenium nanoparticles were then subjected to various characterization techniques such as UV, FTIR, FESEM, EDAX and Zeta potential respectively. Finally the green synthesized SeNps were tested for their cytotoxic effect against L6 rat skeletal muscle cell lines. The pre clinical studies are underway to prove the insulin mimic activity of the selenium nanoparticles.Keywords: Selenium Nanoparticles, Java tea, L6 cell lines.